Application of Responsibility Accounting in the Private Sector - Ainun Arizah; Nur Hanifa; Aulya Muhammad S; Indah Syamsuddin (www.amertainstitute.com, 2024)
This research aims to examine research related to the implementation of accountability accounting in the private sector and provide input regarding further research topics. This research method uses the literature review method and the method developed by Hesford et al (2007), namely the charting the field method. Researchers reviewed research related to responsibility accounting in the private sector published in 15 national accredited by Sinta. The research results show that responsibility accounting plays a role in Corporate Social Responsibility, work performance and managerial assessment, cost control and management tools, performance assessment, and socio-ecology. The effectiveness of responsibility accounting can encourage improved performance, control costs and better decision making. More diverse research related to responsibility accounting will be able to provide additional knowledge regarding the factors that influence the effectiveness of responsibility accounting in the private sector. Further responsibility accounting research can consider research models and other variables that can expand existing research results